2017
DOI: 10.3748/wjg.v23.i19.3522
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of gastric gastrointestinal stromal tumors: A retrospective 10-year single-center experience

Abstract: AIMTo determine the feasibility, safety, and oncological outcome of laparoscopic resection of gastric gastrointestinal stromal tumors (GISTs) based on favorable or unfavorable location.METHODSOur hospital database included 207 patients who underwent laparoscopic removal of gastric GISTs from January 2004 to September 2015. Patient demographics, clinical presentation, surgery, histopathology, postoperative course, and oncological outcomes were reviewed and analyzed.RESULTSGastric GIST in favorable locations was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
1
24
1
Order By: Relevance
“…Laparoscopic wedge resection with or without (eversion technique, as shown in this study) a stapler is the most common and fundamental operative technique, especially for extraluminal G‐SMT located on the gastric body or the greater curvature . As to tumors located near the esophagogastric junction, p‐ring, or on the side of the lesser curvature, this procedure can increase the risk of generating stenosis or deformity in the gastric inlet or outlet . The eversion technique by opening the gastric lumen can involve the potential risk of tumor cell seeding, particularly in patients with GIST with ulceration .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Laparoscopic wedge resection with or without (eversion technique, as shown in this study) a stapler is the most common and fundamental operative technique, especially for extraluminal G‐SMT located on the gastric body or the greater curvature . As to tumors located near the esophagogastric junction, p‐ring, or on the side of the lesser curvature, this procedure can increase the risk of generating stenosis or deformity in the gastric inlet or outlet . The eversion technique by opening the gastric lumen can involve the potential risk of tumor cell seeding, particularly in patients with GIST with ulceration .…”
Section: Discussionmentioning
confidence: 90%
“…In fact, EFTR with complete closure of the gastric‐wall defect using endoclips could be carried out for the lesser/greater curvature side. Conversely, it is inevitable and relatively difficult to operate on lesions located in the lesser curvature side (from the pyloric ring to the cardia) . LR, except for intragastric surgery, requires resection of the attachment of the omentum to the stomach in the excision area to remove the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations about the feasibility of laparoscopy in the surgical treatment of gastric GISTs can be related to the location and the size of the tumor. In the most recent guidelines of the European Society for Medical Oncology, the National Comprehensive Cancer Network (NCCN), and the Asian GIST guidelines, the indication for laparoscopic resection is reduced for lesions in the greater curvature and anterior wall of the gastric body, fundus, and antrum . For those of the lesser curvature, the cardia and the prepyloric region and the risks of stenosis of the lumen postoperatively or nononcological resections in addition to the difficulty in exposing the tumor affect negatively the choice of a laparoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent guidelines of the European Society for Medical Oncology, the National Comprehensive Cancer Network (NCCN), and the Asian GIST guidelines, the indication for laparoscopic resection is reduced for lesions in the greater curvature and anterior wall of the gastric body, fundus, and antrum. 11 For those of the lesser curvature, the cardia and the prepyloric region and the risks of stenosis of the lumen postoperatively or nononcological resections in addition to the difficulty in exposing the tumor affect negatively the choice of a laparoscopic approach. Concerning the limit of tumor's size, several retrospective cohort studies have suggested that laparoscopic resection is feasible and safe for gastric GISTs smaller than 5 cm.…”
Section: Discussionmentioning
confidence: 99%